A triazole derivative elicits autophagic clearance of polyglutamine aggregation in neuronal cells [Corrigendum] - Hsieh CH; Lee LC; Leong WY; Yang TC; Yao CF; Fang K (Drug Design, Development and Therapy, 2016)
Hsieh CH, Lee LC, Leong WY, Yang TC, Yao CF, Fang K. Drug Des Devel Ther. 2016;10:2947–2957.On page 2950, Figure 1, part B has been updated.Read the original article